Removal of Cr(VI) from Wastewater Using Acrylonitrile Grafted Cellulose Extracted from Sugarcane Bagasse - Idrees Khan; Ashraf Ali; Alia Naz; Zenab Tariq Baig; Wisal Shah; Zia Ur Rahman; Tawaf Ali Shah; Kotb A. Attia; Arif Ahmed Mohammed; Yaser M. Hafez (Molecules, 2024)
A highly efficient low-cost adsorbent was prepared using raw and chemically modified cellulose isolated from sugarcane bagasse for decontamination of Cr(VI) from wastewater. First, cellulose pulp was isolated from sugarcane bagasse by subjecting it to acid hydrolysis, alkaline hydrolysis and bleaching with sodium chlorate (NaClO3). Then, the bleached cellulose pulp was chemically modified with acrylonitrile monomer in the presence Fenton’s reagent (Fe+2/H2O2) to carry out grafting of acrylonitrile onto cellulose by atom transfer radical polymerization. The developed adsorbent (acrylonitrile grafted cellulose) was analyzed by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). Both raw cellulose and acrylonitrile grafted cellulose were used for chromium removal from wastewater. The effects of metal ion concentration, pH, adsorbent dose and time were studied, and their values were optimized. The optimum conditions for the adsorption of Cr(VI) onto raw and chemically modified cellulose were: metal ion concentration: 50 ppm, adsorbent dose: 1 g, pH: 6, and time: 60 min. The maximum efficiencies of 73% and 94% and adsorption capacities of 125.95 mg/g and 267.93 mg/g were achieved for raw and acrylonitrile grafted cellulose, respectively. High removal efficiency was achieved, owing to high surface area of 79.92 m2/g and functional active binding cites on grafted cellulose. Isotherm and kinetics studies show that the experimental data were fully fitted by the Freundlich isotherm model and pseudo first-order model. The adsorbent (acrylonitrile grafted cellulose) was regenerated using three different types of regenerating reagents and reused thirty times, and there was negligible decrease (19%) in removal efficiency after using it for 30 times. Hence, it is anticipated that acrylonitrile could be utilized as potential candidate material for commercial scale Cr(VI) removal from wastewater.